2022
DOI: 10.3390/su142114145
|View full text |Cite
|
Sign up to set email alerts
|

Flash Flood Hazard Mapping Using Remote Sensing and GIS Techniques in Southwestern Saudi Arabia

Abstract: Flash flooding is one of the most significant natural disasters in arid/hyperarid regions and causes vast property damage and a large number of deaths. For mitigating and reducing flood risks, data from several remote sensing satellite images—Shuttle Radar Topography Mission (SRTM) Digital Elevation Model (DEM), Landsat 8 Operational Land Imager (OLI), and Tropical Rainfall Measuring Mission (TRMM)—were prepared and combined through a GIS-based multicriteria decision-making technique to test and delineate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 72 publications
3
18
0
Order By: Relevance
“…It was found that the outlet of this sub-basin crosses the Highway of King Abdulaziz and may expose this road to a major flood risk. This finding aligned with another similar study, which identified the same locations as sites with extreme to very high levels of flood risk [2]. Flash floods in these areas have severely affected cities and infrastructure like roads and parking lots, causing massive losses of property [2].…”
Section: Flood Hydrographs and Peak Runoffsupporting
confidence: 88%
See 2 more Smart Citations
“…It was found that the outlet of this sub-basin crosses the Highway of King Abdulaziz and may expose this road to a major flood risk. This finding aligned with another similar study, which identified the same locations as sites with extreme to very high levels of flood risk [2]. Flash floods in these areas have severely affected cities and infrastructure like roads and parking lots, causing massive losses of property [2].…”
Section: Flood Hydrographs and Peak Runoffsupporting
confidence: 88%
“…Its location lies within the latitudinal range of 18 • 13 ′ 44.36 ′′ -19 • 2 ′ 55.39 ′′ N and the longitudinal range of 41 • 21 ′ 18.07 ′′ -42 • 29 ′ 47.28 ′′ E, a distance of about 141 km. This area is largely composed of basalt rocks [2]. The main city in the area is Muhayil, located in the center of the wadi catchment.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as a result of the climate crisis, identifying flood-prone locations and assessing the linkages between disasters and the environment have become essential and urgent needs in urban flood risk management. Therefore, studies that determine potential flood impact areas and disaster damage using techniques such as geographic information systems [10], remote sensing [11], and hydrological modeling [12] are crucial for managers and decision makers.…”
Section: Introductionmentioning
confidence: 99%
“…Flash floods are one of the major natural threat crises that cause loss and damage of services and infrastructure, human, and economic activities due to an excess of heavy rainfalls that occur quickly and over a short period of time. This is especially true in areas with rugged terrain (Zhang et al, 2015;Elkhrachy, 2015;Abdelkareem, 2017;Zhao et al, 2018;Abdelkareem and Al-Arifi, 2021;Alarifi et al, 2022). Runoff levels have a positive impact on overland flow and speed up its response time.…”
Section: Introductionmentioning
confidence: 99%